Die veelkantige nawerking van Luther in Halle- Wittenberg: "n Leksikografiese bydrae tot Reformasie 500 oor August Hermann Francke en Paul Tillich - Wyk, Ignatius W. C.Van (HTS teologiese studies, 2017)
The article is a lexicographic contribution to Reformation 500. Two relatively unknown Lutheran theologians to the South African public, namely August Francke and Paul Tillich, are presented here. Both were students and lecturers at the Martin Luther University of Halle-Wittenberg. Both of them wanted to be known as Lutheran theologians. The two are totally opposites. Francke was a practical theologian who initiated many diaconal projects that are still active after 300 years. Tillich was a philosopher of religion and a systematic theologian. He made a huge contribution in promoting Lutheran ideas to secular society in the United States of America.